Effects of tillage systems and organic manures on soybean (Glycine max) yield and quality - HEIDARI, GHOLAMREZA; MOHAMMADI, KHOSRO; SOHRABI, YOUSEF (The Indian Journal of Agricultural Sciences, 2020)
The study was conducted to analyze the responses of soybean [Glycine max (L.) Merr.] seed yield and quality to tillage and fertilization in Sanandaj, Iran over two years (2012 and 2013). The experiments were arranged in split-plot, based on randomized complete block design with three replications. Main plots consisted of tillage systems including conventional tillage (CT), minimum tillage (MT), and no-tillage (NT). Eight fertilization methods were employed in the sub-plots including (F1): farmyard manure (FYM); (F2): compost; (F3): chemical fertilizers; (F4): FYM + compost; (F5): FYM + chemical fertilizers; (F6): compost + chemical fertilizers; (F7): FYM + compost + chemical fertilizers; and (F8): Control (without fertilizer). The highest number of pods and seeds per plant and grain yield were obtained in MT-F7 treatment, in which compost, manure, and chemical fertilizers were applied simultaneously in a balanced manner under reduced tillage system. The highest content of seed oil belonged to farmyard manure application. The highest content of seed protein was related to combined fertilizer application and complete chemical fertilizer. This treatment can be considered as a step toward sustainable agriculture. We concluded that applying organic manures along with moderated chemical fertilizers and employing reduced tillage systems increased soybean yield.